Assessing the influence of Chinese foreign direct investments on Nigeria’s industrial productivity - Sheng, Du; Singh, Gurdip Kaur Saminder; Dan, Washima Che; Joshi, Veena (Edelweiss Applied Science and Technology, 2025)
This study investigates the productivity impact of Chinese foreign direct investment (FDI) within Nigeria’s Free Trade Zones (FTZs), focusing on how Chinese investment, exports, and imports influence Nigeria’s overall productivity growth. The research employs a quantitative design using secondary data drawn from the United Nations Conference on Trade and Development (UNCTAD), the National Bureau of Statistics (NBS), and the Ministry of Commerce of the People’s Republic of China. The data were analyzed through Ordinary Least Squares (OLS) regression to determine the relationship between Chinese economic activities and productivity outcomes in Nigeria’s FTZs. Results reveal that Chinese FDI and imports from Nigeria exert no significant effect on productivity. In contrast, Chinese exports to Nigeria show a positive and significant impact, suggesting that increased trade inflows contribute to productivity enhancement. The study concludes that trade relations, rather than investment inflows alone, are key drivers of productivity improvement. Strengthening Nigeria’s FTZ regulatory framework, particularly regarding transparency, accountability, and labor and environmental standards, can maximize the developmental benefits of Chinese engagement.